The evolution of star formation in QSOs according to WISE. Issue Volume 15:Issue S359(2020) (March 2019) - Cutiva-Alvarez, K. A.; Coziol, R.; Torres-Papaqui, J. P.; Andernach, H.; Robleto-Orús, A. C.
Abstract: Using WISE data, we calibrated the W2-W3 colors in terms of star formation rates (SFRs) and applied this calibration to a sample of 1285 QSOs with the highest flux quality, covering a range in redshift from z ˜ 0.3 to z ˜ 3.8. According to our calibration, the SFR increases continuously, reaching a value at z ˜ 3.8 about 3 times higher on average than at lower redshift. This increase in SFR is accompanied by an increase of the BH mass by a factor 100 and a gradual increase of the mean Eddington ratio from 0.1 to 0.3 up to z ˜ 1.5 – 2.0, above which the ratio stays constant, despite a significant increase in BH mass. Therefore, QSOs at high redshifts have both more active BHs and higher levels of star formation activity.